La crisi dello stato di diritto in Serbia tra manipolazioni elettorali, corruzione e resistenza della società civile (Nuovi Autoritarismi e Democrazie: Diritto, Istituzioni, Società (NAD-DIS), 2025)
The Crisis of the Rule of Law in Serbia among Electoral Manipulations, Corruption, and Civil Society’s ResistanceThe recent protests in Serbia against the corruption have been highlighting the fragility of the system, since it does not appear anymore a democratic model. After December 2023 general elections, Serbian situation has rekindled the concerns of many international observatories and of the European Union. Serbia is actually classified as an “illiberal democracy” or an “electoral autocracy”.
Keywords: Serbia; political crisis; elections; populism; European Union (relationships with)